2020
DOI: 10.1002/jcp.30224
|View full text |Cite
|
Sign up to set email alerts
|

PLD1 and PLD2 differentially regulate the balance of macrophage polarization in inflammation and tissue injury

Abstract: Phospholipase D (PLD) isoforms PLD1 and PLD2 serve as the primary nodes where diverse signaling pathways converge. However, their isoform‐specific functions remain unclear. We showed that PLD1 and PLD2 selectively couple to toll‐like receptor 4 (TLR4) and interleukin 4 receptor (IL‐4R) and differentially regulate macrophage polarization of M1 and M2 via the LPS–MyD88 axis and the IL‐4–JAK3 signaling, respectively. Lipopolysaccharide (LPS) enhanced TLR4 or MyD88 interaction with PLD1; IL‐4 induced IL‐4R or JAK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
0
24
1
Order By: Relevance
“…Polarization with IL-4 increased the rate of choline uptake (Figure 1D) and incorporation into PC (Figure 1E), without changing choline transport affinity or sensitivity to inhibition (supplemental Figure 1A-B). Moreover, while select phospholipases are upregulated in M[IL-4] 25 we observed no difference in the rate of PC degradation (supplemental Figure 1C), suggesting an overall increase in cellular PC content in IL-4-polarized macrophages, which completely mirrored the effects of LPS polarization. 4…”
Section: Il-4 Upregulates Choline Metabolism In Macrophagesmentioning
confidence: 74%
“…Polarization with IL-4 increased the rate of choline uptake (Figure 1D) and incorporation into PC (Figure 1E), without changing choline transport affinity or sensitivity to inhibition (supplemental Figure 1A-B). Moreover, while select phospholipases are upregulated in M[IL-4] 25 we observed no difference in the rate of PC degradation (supplemental Figure 1C), suggesting an overall increase in cellular PC content in IL-4-polarized macrophages, which completely mirrored the effects of LPS polarization. 4…”
Section: Il-4 Upregulates Choline Metabolism In Macrophagesmentioning
confidence: 74%
“…Much effort has been devoted to uncovering the function of PLD2 in speci c situations, such as disease, which makes PLD2 function more predictable than expected [29]. Furthermore, because PLD2 is ubiquitously expressed in most cell types, more complex studies using knockout animal models are required to reveal the cell-, tissue-, and organ-speci c functions of PLD2 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Abdulnour et al recently demonstrated that PLD2 expression is associated with mortality in patients with ARDS and that PLD2 expression is decreased in murine self-resolving ALI. PLD2 de ciency reduces ALI severity and is associated with the increased recruitment of macrophages with enhanced phagocytosis and decreased neutrophil production of reactive oxygen species (ROS) [29]. To our knowledge, the role of PLD2 in ARDS pathogenesis has not been elaborated [32].…”
Section: Discussionmentioning
confidence: 99%
“…While PLD1 is present at the plasma membrane and intracellular vesicles, PLD2 seems to localize at perinuclear regions [ 21 ]. Importantly, it has recently been described that during activation of macrophages by LPS, PLD1, but not PLD2, associates with TLR4 and MyD88, increasing its activity [ 20 ]. It is thus plausible that the TLR4/MyD88/PLD1 axis mediates increases in PA pools that serve as substrates for lipin-1 during the events of macrophage proinflamatory activation and sepsis development described in this study.…”
Section: Discussionmentioning
confidence: 99%